2001
DOI: 10.1093/cercor/11.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic Organization of Human Secondary Somatosensory Cortex

Abstract: This fMRI study investigated the human somatosensory system, especially the secondary somatosensory cortex (SII), with respect to its potential somatotopic organization. Eight subjects received electrical stimulation on their right second finger, fifth finger and hallux. Within SII, the typical finding for both fingers was a representation site within the contralateral parietal operculum roughly halfway between the lip of the lateral sulcus and its fundus, whereas the representation site of the hallux was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
162
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(191 citation statements)
references
References 78 publications
27
162
2
Order By: Relevance
“…Another finger representation is located medial and superior to the lip and face representations in the postcentral gyrus, and it extends into the ventral postcentral sulcus. We suggest that this finger representation overlaps with the ventral part of S-I digit representations (27,28) and a parietal hand area at the confluence of ventral postcentral sulcus and anterior intraparietal sulcus (25,(30)(31)(32). An area of the toe representation partially overlaps with the superior part of the face representation in the central sulcus bilaterally.…”
Section: Resultsmentioning
confidence: 78%
“…Another finger representation is located medial and superior to the lip and face representations in the postcentral gyrus, and it extends into the ventral postcentral sulcus. We suggest that this finger representation overlaps with the ventral part of S-I digit representations (27,28) and a parietal hand area at the confluence of ventral postcentral sulcus and anterior intraparietal sulcus (25,(30)(31)(32). An area of the toe representation partially overlaps with the superior part of the face representation in the central sulcus bilaterally.…”
Section: Resultsmentioning
confidence: 78%
“…The obtained BSM results thus likely reflect a compound measure of skeletomuscular and visceral sensations, as well as the effects of autonomic nervous system, which the individuals 0 0 cannot separate. As several subareas of the human cortical somatosensory network contain somatotopic representations of the body (24), specific combinations of somatosensory and visceral afferent inputs could play a central role in building up emotional feelings. It must nevertheless be emphasized that we do not argue that the BSMs highlighted in this series of experiments would be the only components underlying emotional experience.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately adjacent to VIP, we found strong evidence for passive finger somatotopy in an area just inferior to the confluence of postcentral and intraparietal sulci. This area has been labeled PP (posterior parietal) by Ruben et al (2001) and "PostCS" region by Culham (2003). We suggest that this area may correspond to a human homologue of AIP (Binkofski et al, 1998;Culham et al, 2006;Frey et al, 2005;Lewis and Van Essen, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using fMRI have revealed somatotopic representations of the hand, fingers, wrist, elbow, shoulder, foot, toes, lips, and tongue in human brains (Alkadhi et al, 2002;Beisteiner et al, 2001;Blankenburg et al, 2003;Dechent and Frahm, 2003;Francis et al, 2000;Gelnar et al, 1998;Golaszewski et al, 2006;Hanakawa et al, 2005;Hlustik et al, 2001;Kurth et al, 2000;Lotze et al, 2000;McGlone et al, 2002;Miyamoto et al, 2006;Moore et al, 2000a;Overduin and Servos, 2004;Ruben et al, 2001;Servos et al, 1998;Stippich et al, 1999Stippich et al, , 2004van Westen et al, 2004; also see reviews in Burton, 2002). The human face contains important sensory organs and is essential for verbal and nonverbal communications in daily life.…”
Section: Introductionmentioning
confidence: 99%